2018
DOI: 10.1002/2017je005419
|View full text |Cite
|
Sign up to set email alerts
|

Equatorial Oscillation and Planetary Wave Activity in Saturn's Stratosphere Through the Cassini Epoch

Abstract: Thermal infrared spectra acquired by Cassini/Composite InfraRed Spectrometer (CIRS) in limb‐viewing geometry in 2015 are used to derive 2‐D latitude‐pressure temperature and thermal wind maps. These maps are used to study the vertical structure and evolution of Saturn's equatorial oscillation (SEO), a dynamical phenomenon presenting similarities with the Earth's quasi‐biennal oscillation (QBO) and semi‐annual oscillation (SAO). We report that a new local wind maximum has appeared in 2015 in the upper stratosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 36 publications
5
53
1
Order By: Relevance
“…are likely to be significant within Saturn's tropics. This is compliant with the recent analysis by Guerlet et al (2018), based on Cassini CIRS observations, which shows a complex structure at a pressure level of 150 mbar; interestingly, what appears as a wavenumber-3 Rossby mode dominate in the upper stratosphere (0.5 to 5 mbar), possibly indicating conditions for breaking at this level or below for the other modes. Unless the wavenumber-2 signal found by Achterberg and Flasar (1996) is actually eastward-propagating at phase speeds about 1600 m s −1 (the fast planetary modes were discarded by this study in favour of slower, more plausible, Rossby modes), the prominent wavenumber-2 westward-propagating Yanai wave in our Saturn DYNAMICO GCM simulation remains to be evidenced in observations.…”
Section: Equatorial Wavessupporting
confidence: 91%
“…are likely to be significant within Saturn's tropics. This is compliant with the recent analysis by Guerlet et al (2018), based on Cassini CIRS observations, which shows a complex structure at a pressure level of 150 mbar; interestingly, what appears as a wavenumber-3 Rossby mode dominate in the upper stratosphere (0.5 to 5 mbar), possibly indicating conditions for breaking at this level or below for the other modes. Unless the wavenumber-2 signal found by Achterberg and Flasar (1996) is actually eastward-propagating at phase speeds about 1600 m s −1 (the fast planetary modes were discarded by this study in favour of slower, more plausible, Rossby modes), the prominent wavenumber-2 westward-propagating Yanai wave in our Saturn DYNAMICO GCM simulation remains to be evidenced in observations.…”
Section: Equatorial Wavessupporting
confidence: 91%
“…In our simulation, the modal spectra E (n, m) show that modes m = 2 and 3 make a dominant contribution to the residual spectrum, suggesting strongly energetic waves that propagate in the zonal direction. Spiga et al (2020) identified indeed wavenumber-2 and wavenumber-3 Rossby waves and Rossby-gravity waves, with possible relation to wave patterns observed by either Voyager (Achter-berg and Flasar, 1996) or Cassini (Guerlet et al, 2018). However, as of now, a complete statistical analysis using Saturn direct observations is yet to be performed on the most recent images.…”
Section: Spectral Analysis Of the Wind Fieldmentioning
confidence: 93%
“…The Cassini ISS data corresponds to two different layers sensed in CB filters sensitive to the top of the main cloud layer and MT filters sensitive to the upper hazes in the lower stratosphere at ∼ 60 mbar. Motions at both layers are very different in the equator for the same years and the narrow and intense jet in the upper hazes and its temporal variations could be related to the equatorial thermal oscillations (Fouchet et al, 2008;Orton et al, 2008;Guerlet et al, 2018). The Cassini VIMS data senses deeper clouds at roughly 2 bar, where temporal changes are not expected.…”
Section: Winds and Atmospheric Features In The Ezmentioning
confidence: 92%
“…The Equatorial Zone (EZ) is particularly complex, as it is a region known to have temporal changes in the wind field at cloud level and in its vertical wind shear (Sánchez-Lavega et al, 2003;Porco et al, 2005) over most of the troposphere, as well as quasi-periodic thermal oscillations in the stratosphere that occur both in altitude and in time (Fouchet et al, 2008;Orton et al, 2008;Guerlet et al, 2018). The quasi-periodic oscillations of the stratosphere where disrupted with the development of the 2010-2011 Great White Spot (Fletcher et al, 2017) further complicating the dynamics of the EZ.…”
Section: Winds and Atmospheric Features In The Ezmentioning
confidence: 99%